Geography syllabus June 1987 - Caribbean Examinations Council (Caribbean Examinations Council, 1987)
The CXC Geography syllabus is designed to be covered in the final two years of a normal five-year secondary school course. It is expected therefore that a groundwork of skills and abilities related to the subject would have been laid in the first three years of the school course. The Ecosystem ad Spatial Organisation paradigms have been used in formulating the syllabus. The former provides the basic structure, while major concepts are derived from the latter.
Keywords: CXC syllabus